2011
DOI: 10.1210/jc.2010-2135
|View full text |Cite
|
Sign up to set email alerts
|

Contributors to Secondary Osteoporosis and Metabolic Bone Diseases in Patients Presenting with a Clinical Fracture

Abstract: At presentation with a fracture, 26.5% of patients have previously unknown contributors to SECOB, which are treatable or need follow-up, and more than 90% of patients have an inadequate vitamin D status and/or calcium intake. Systematic screening of patients with a recent fracture identifies those in whom potentially reversible contributors to SECOB and calcium and vitamin D deficiency are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 32 publications
6
91
2
5
Order By: Relevance
“…Serum testosterone, Pi, or IGFBP3 values did not correlate with any of the DXA-derived bone parameters and it thus remains unknown how these risk factors may influence bone health in ALL survivors during their later adulthood. Male hypogonadism is a significant risk factor for osteoporosis (28). It is important to ensure proper replacement therapy and follow the compliance in adult ALL survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Serum testosterone, Pi, or IGFBP3 values did not correlate with any of the DXA-derived bone parameters and it thus remains unknown how these risk factors may influence bone health in ALL survivors during their later adulthood. Male hypogonadism is a significant risk factor for osteoporosis (28). It is important to ensure proper replacement therapy and follow the compliance in adult ALL survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary osteoporosis is defined as bone loss that results from specific, well-defined, clinical disorders or medical treatments (1). The prevalence of secondary osteoporosis, in both men and women, is widely debated (1,2,3,4,5,6,7,8). In some studies 20-30% of postmenopausal women and more than 50% of men with osteoporosis are affected with the secondary form of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…subclinical hypercortisolism (SH), celiac disease, etc.) (1,3,5,6,7,16). Moreover, the criteria used to define which patient should undergo additional evaluation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, P2X7 receptors were shown to mediate stimulation of periosteal and cancellous bone formation and the inhibition of cancellous bone resorption during growth [115]. The P2X7 receptor is highly polymorphic and a number of studies have shown that single nucleotide polymorphisms (SNPs) of the P2X7 receptor gene are associated with fracture risk, decreased bone mineral density and osteoporosis (see [222][223][224]365]). P2X7 receptors are also involved in the complex chain of events leading to the formation of human osteoclasts, and it was suggested that P2X7 receptor antagonists may be valuable for the management of osteoporosis and with disorders of remodelling, where there is reduced bone mass [366,367].…”
Section: Osteoporosismentioning
confidence: 99%